Thermal Evaluation of a New Bio-based Insulation Material Using Rice Waste - Maatouk Khoukhi; Abeer Dar Saleh (Science and Technology: Developments and Applications Vol. 3, 2025)
Buildings are the largest consumer of energy among other sectors. One of the most important challenges of future buildings is the reduction of energy consumption in all their life phases, from construction to demolition. Although many advanced insulation materials have been recently developed, very few are eco-friendly, and their production requires a substantial amount of energy and complex manufacturing processes. To address this issue, a new cheap bio-insulation material with huge commercialization potential and environmental footprint is proposed. The main idea is to develop a new material, which is environmentally friendly insulation from waste rice grain. A set of experiments was subsequently carried out to identify the best rice type and the optimal range for the most influential parameters (sample amount, temperature, and moisture level). Our findings revealed that short-grained rice exhibited greater puffing ability and was thus adopted in further material optimization experiments. These assessments indicated that the most optimal thermal conductivity of the insulation material and the highest puffing ratio was attained at 12-15% moisture, 260-270 oC temperature, and 15-18 g sample weight. The thermal conductivity and thermal performance of samples obtained using these parameters were similar to those of common insulation materials such as polystyrene.